CREATION – FROM PRE-ETERNITY TO PROBABILITY (AL-JADID TAHAFUT AL-FALASIFAH) A CONTRIBUTION TO THE HISTORY OF MUSLIM PHILOSOPHY - Siddiqui, Naseeb Ahmed (UIN Ar-Raniry, 2017)
It is not the physical world consist in itself as to what reality is, but proof of ultimate reality. Reality does not change by changing the process rather attributable quality named from A to B or This to that but essence remains the same. Process in metaphysics has two inseparable parts according to philosophers, cause and effect, which in any case intrinsic to every event coming into being. Denying either one makes impossibility of event. Once cause with all necessary condition fulfilled, cannot delay its effect by necessity, which is the sole premise with philosophers to assume worlds pre-eternity. On the contrary, according to Islamic theologians, it is not necessary and condition for event to have causal connection and it is possible to delay effect in presence of cause also and this is possible in conventional as well as rational and reasoning level. The central issue rose by Imam Al-Gazali (rahmatullahali) in his `Tahafut Al-falasifa concerning the world’s pre-eternity rotate around the cause and effect. He showed the incoherence of arguments posed by philosophers and proposed that it’s possible to delay the effect. Now, after 800 years, creation already unveiled mysteries in the form, which both the parties (Philosophers and theologians) did not know. However, who won the debate over world’s pre-eternity is still open. This paper will try to fill that gap by attempting direct discussion of Tahafut Al-falasifa on the issue of world pre-eternity, considering cause and effect as central debate and will show that what Imam Al-Gazali (rahmatullahali) proposed was correct: The delay in effect with cause is possible. This will be a contribution to the Islamic theology collecting physical facts from science, which anyhow reached to the same level where it meets metaphysics. This will be the latest debate on the issue, and provide new insights on some of core results of scientific theories, which are not considered yet.